Should Pollution Taxes be Targeted at Income Redistribution? - Bas Jacobs; Rick van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper analyses optimal corrective taxation and optimal income redistribution. Under general utility functions, the Pigouvian pollution tax is higher if pollution damages disproportionally hurt the poor due to equity weighting of pollution damages. Moreover, optimal pollution taxes should be set below the Pigouvian tax if the poor spend a disproportionate fraction of their income on polluting goods. However, if preferences for commodities are of the Gorman (1961) polar form, optimal pollution taxes should follow the first-best rule for the Pigouvian corrective tax even if the government wants to redistribute income and the poor spend a disproportional part of their income on polluting goods. The often-used quasi-linear, CES and Stone-Geary utility functions all belong to the Gorman polar class. If preferences are Gorman polar, and if pollution taxes are not optimized, Pareto-improving green tax reforms exist that move the pollution tax closer to the Pigouvian tax. Simulations demonstrate that optimal corrective taxes should be Pigouvian if the demand for polluting goods is derived from a LES demand system, but deviate from the Pigouvian taxes if demand for polluting goods demand is derived from a PIGLOG demand system.
Keywords: H21; H23; Q54; 330; redistributive taxation; corrective pollution taxation; Gorman polar form; Stone-Geary preferences; PIGLOG preferences; green tax reform